A note on local industry asset betas for cost of capital computations - David J. Bradfield (South African Journal of Business Management, 1998)
Based on the premise that portfolio betas are more reliable than individual betas, it is advocated that industry asset betas rather than individual betas be used when proxies are required in cost of capital calculations. In this article local industry asset betas are empirically estimated and contrasted to US estimates. The results reveal that not all USA industry risks are translatable to the SA context and thus attempts should be made to estimate industry risks locally for cost of capital computations.
Keywords: 650